Human Multipotent Adult Progenitor Cells Are Nonimmunogenic and Exert Potent Immunomodulatory Effects on Alloreactive T-Cell Responses. Issue 10 (October 2013) - Jacobs, Sandra A.; Pinxteren, Jef; Roobrouck, Valerie D.; Luyckx, Ariane; Van't Hof, Wouter; Deans, Robert; Verfaillie, Catherine M.; Waer, Mark; Billiau, An D.; Van Gool, Stefaan W.
Multipotent adult progenitor cells (MAPCs) are bone marrow-derived nonhematopoietic stem cells with a broad differentiation potential and extensive expansion capacity. A comparative study between human mesenchymal stem cells (hMSCs) and human MAPCs (hMAPCs) has shown that hMAPCs have clearly distinct phenotypical and functional characteristics from hMSCs. In particular, hMAPCs express lower levels of MHC class I than hMSCs and cannot only differentiate into typical mesenchymal cell types but can also differentiate in vitro and in vivo into functional endothelial cells. The use of hMSCs as cellular immunomodulatory stem cell products gained much interest since their immunomodulatory capacities in vitro became evident over the last decade. Currently, the clinical grade stem cell product of hMAPCs is already used in clinical trials to prevent graft-versus-host disease (GVHD), as well as for the treatment of acute myocardial infarct, ischemic stroke, and Crohn's disease. Therefore, we studied the immune phenotype, immunogenicity, and immunosuppressive effect of hMAPCs in vitro. We demonstrated that hMAPCs are nonimmunogenic for T-cell proliferation and cytokine production. In addition, hMAPCs exert strong immunosuppressive effects on T-cell alloreactivity and on T-cell proliferation induced by mitogens and recall antigens. This immunomodulatory effect was not MHC restricted, which makes off-the-shelf use promising. The immunosuppressive effect of hMAPCs is partially mediated via soluble factors and dependent on indoleamine 2, 3-dioxygenase (IDO) activity. At last, we isolated hMAPCs, the clinical grade stem cell product of hMAPCs, named MultiStem, and hMSCs from one single donor and observed that both the immunogenicity and the immunosuppressive capacities of all three stem cell products are comparable in vitro. In conclusion, hMAPCs have potent immunomodulatory properties in vitro and can serve as a valuable cell source for the clinical use of immunomodulatory cellular stem cell product.